Studies on Pd(0), Pt(0), Rh(I), Ni(II), Co(II) and Zr(IV) Complexes of 4-Amino-3-hydrazino-5-mercapto-1,2,4-triazole - Pandey, R.N.; Sharma, R.N.; Sahay, A.N.; Roy Choudhary, Rita; Das, J.N. (Asian Journal of Chemistry, 2010)
Complexes of 4-amino-3-hydrazino-5-mercapto-1,2,4-triazole(AHtTh) have been prepared with Pd(0), Pt(0), Rh(I), Ni(II), Co(II) and Zr(IV) and the structures of the complexes have been investigated by physico-chemical methods. Bonding of the ligand occurs through thione tautomeric form in Pd(0), Pt(0) and Zr(IV) but the ligand interacts with thiol form at pH 7 resulting in deprotonation of thiol hydrogen in Rh(I), Co(II), Ni(II) and few Zr(IV) complexes. Physico-chemical data suggest tetrahedral structure for Pd(0) and Pt(0), square planar for Rh(I) and octahedral configuration for Co(II), Ni(II) and Zr(IV) complexes.